Explicit Asymptotic Velocity of the Boundary between Particles and Antiparticles. (19th September 2012) - Malyshev, V. A.; Manita, A. D.; Zamyatin, A. A.
Abstract : On the real line initially there are infinite number of particles on the positive half line, each having one ofK -negative velocitiesv 1 ( + ), …, v K ( + ) . Similarly, there are infinite number of antiparticles on the negative half line, each having one ofL -positive velocitiesv 1 ( - ), …, v L ( - ) . Each particle moves with constant speed, initially prescribed to it. When particle and antiparticle collide, they both disappear. It is the only interaction in the system. We find explicitly the large time asymptotics ofβ ( t ) —the coordinate of the last collision beforet between particle and antiparticle.